Too turgid to quit: examining the role of leaf turgor loss point in Bukit Timah forest dynamics - Soh, Sun Yi (Nanyang Technological University, 2022)
The primary forest at Bukit Timah Nature Reserve (BTNR) has undergone substantial floristic compositional shifts over the past 29 years, with the relative abundances of many tree species changing significantly. Previous studies suggested a link between these population changes and water stress, but this had never been tested. In this study, we examined the relationship between these compositional changes to leaf water potential at turgor loss point (TLP), a key functional trait that is associated with the drought-tolerance of trees. As climate change has been increasing the frequency and intensity of dry spells in Singapore in recent decades, I hypothesised that tree species that were more drought-tolerant—which would have a more negative TLP—would become increasingly abundant in the plot. I also explored the variation of TLP within species, especially across trees of different age classes. Through my study I found that TLP has indeed a negative correlation with species relative abundance changes as hypothesised, though the correlation was weak. However, TLP had a stronger correlation with the relative abundance changes than all other leaf traits analysed. Notably, I found that the variability of TLP was much greater in some species than others and TLP values within species were also not always constant across age classes. These results suggest the presence of significant plasticity of TLP within species, or even within individuals. This was the first study to my knowledge to incorporate hydraulic functional traits of trees to understand the forest dynamics at BTNR.